Development of accidental blast analysis module for 3D applied element method - Aliyar, Mohamed Abzal Ilahi; Krishna, Chaitanya; Panon Latcharote; Pennung Warnitchai; Thanakorn Pheeraphan; AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
Blast loads from accidental surface explosions can cause severe local damage and even progressive collapse in buildings, making accurate prediction tools essential for safety assessment and design. This study develops, verifies, and validates a three-dimensional blast analysis module within the Applied Element Method (AEM) to simulate building component response under such events. The module, implemented in Fortran, calculates load parameters directly from UFC 3-340-02 and generates pressure{u2013}time histories for each exposed face of the structure front, side, roof, and rear before applying them to a 3D AEM model.Verification focused on confirming the accuracy of the blast loading routines and the structural response formulation. Predicted incident and reflected overpressures matched reference data and Extreme Loading for Structures (ELS) results at different heights, showing correct spatial decay of blast loads. The pressure{u2013}time histories reproduced both the positive and negative phases of the waveform, with peak magnitude, rise time,and decay closely aligned with literature values. Force-controlled benchmark cases including ramp, triangular, step-with-decay, and blast-type exponential loads were also simulated, where displacement responses from the developed module agreed almost exactly with ELS outputs, confirming correct time integration and contact modeling.Validation was carried out against experimental data. For a reinforced concrete column tested by Farouk Siba (2014), the module replicated measured pressure{u2013}time histories and displacement{u2013}time responses at 1.0 m and 1.5 m heights. For a reinforced concrete frame with masonry infill from Saleh et al. (2016), the simulated damage patterns including front-face detachment, rear-side debris scatter, and crack localization matched both experimental observations and high-fidelity FEM predictions.Overall, the developed AEM-Blast module demonstrated the ability to realistically capture blast pressure fields, complete pressure wave phases, and progressive structural damage leading up to collapse. The results confirm its suitability for engineering-level blast resilience assessments and provide a solid foundation for future enhancements to handle more complex loading environments.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2025
Keywords: Blast effect